RESEARCH ON SUBMERGED FRICTION STIR PROCESSING OF EN AW 6082 ALUMINUM ALLOY (Nonconventional Technologies Review, 2025)
Submerged friction stir processing (SFSP) is a variant of processing the surfaces of metallic materials that uses the liquid medium to ensure a process temperature that does not thermally overload the materials to be processed or the processing tool. SFSP processing aims at local modification of the properties of the materials to be processed. The paper presents results of experimental research carried out at ISIM Timisoara on submerged friction stir processing (SFSP) of the 5mm thick EN AW 6082 aluminum alloy. In the SFSP processing experiments, multiple processing rows were performed with their partial overlap. The evaluation of the processed material consisted of visual examination and with penetrating radiation, structural analysis, mechanical tensile tests and bending tests, positive results the results being achieved.
Keywords: submerged friction stir processing; EN AW 6082 aluminum alloy; experiments; structural analysis; mechanical properties; SFSP